Efficacy of Biostimulants Formulated With Pseudomonas putida and Clay, Peat, Clay-Peat Binders on Maize Productivity in a Farming Environment in Southern Benin - Agbodjato, Nadège Adoukè; Adoko, Marcel Yévèdo; Babalola, Olubukola Oluranti; Amogou, Olaréwadjou; Badé, Farid T.; Noumavo, Pacôme A.; Adjanohoun, Adolphe; Baba-Moussa, Lamine (Frontiers in Sustainable Food Systems, 2021)
Maize plays a vital role in Benin's agricultural production systems. However, at the producer-level, yields are still low, although the production of this cereal is necessary for food security. The aims of this study were to assess the efficacy of solid biostimulants formulated from the rhizobacteria Pseudomonas putida and different binders on maize cultivation in the farming environment in three (03) study areas in South Benin. For this purpose, three (03) biostimulants were formulated based on Pseudomonas putida and the clay, peat and clay-peat combinations binders. The experimental design was a randomized block of four (04) treatments with 11 replicates per study area. Each replicate represented one producer. The trials were set up at 33 producers in the study areas of Adakplamè, Hayakpa and Zouzouvou in Southern Benin. The results obtained show that the best height, stem diameter, leaf area as obtained by applying biostimulants based on P. putida and half dose of NPK and Urea with respective increases of 15.75, 15.93, and 15.57% as compared to the full dose of NPK and Urea. Regarding maize yield, there was no significant difference between treatments and the different study areas. Taken together, the different biostimulants formulations were observed to be better than the farmers' practice in all the zones and for all the parameters evaluated, with the formulation involving Pseudomonas putida on the clay binder, and the half-dose of NPK and Urea showing the best result. The biostimulant formulated based on clay + Pseudomonas putida could be used in agriculture for a more sustainable and environmentally friendly maize production in Benin.